مساهمة المسؤولية الاجتماعية في تحقيق ولاء الزبون دراسة حالة مؤسسة اتصالات الجزائر _سوق اهراس _ - سارة بوشكاوي; عزالدين محفوظي (My University, 2022)
We have reached a social responsibility in its various dimensions (the economic dimension, the environmental dimension, the legal dimension, the ethical dimension, the charitable dimension, the social dimension) in achieving customer loyalty in Algeria Telecom by clarifying the nature of corporate social responsibility and the foundations and practices of corporate social responsibility, as well as what Customer loyalty and how to achieve it and the foundations of developing the relationship with the customer and building his loyalty, and highlighting the relationship between them with regard to the theoretical aspect of the study. As for the practical aspect, our study relied on a paper questionnaire that included questions related to three axes that lead to the idea of the problem of the study and its hypotheses, and we concluded that there is a role of social responsibility in achieving customer loyalty in Algeria Telecom. .................................................... قد توصلنا الى مساهمة المسؤولية الاجتماعية بأبعادها المختلفة )البعد الاقتصادي ،البعد البيئي ،البعد القانوني ،البعد الأخلاقي ،البعد الاجتماعي( في برقيق ولاء الزبائن في مؤسسة اتصالات الجزائر من خلال تبيان ماىية المسؤولية الاجتماعية للمؤسسات وأسس وممارسات المسؤولية الاجتماعية للمؤسسات، وأيضا ماىية ولاء الزبون وكيفية برقيقو وأسس تطوير العلاقة مع الزبون وبناء ولائه ، وإبراز العلاقة بينهما هذا فيما يخص الجانب النظري من الدراسة . أما فيما يخص الجانب التطبيقي اعتمدت دراستنا على استبيان ورقي تضمن أسئلة متعلقة بثلاثة محاور تصب في فكرة إشكالية الدراسة وفرضياتها ،وقد توصلنا إلى أن هناك دور المسؤولية الاجتماعية بأبعادها في برقيق ولاء الزبون في مؤسسة اتصالات الجزائر.